Risk Factors of Poor Glycaemic Control among Patients with Type 2 Diabetes Mellitus at the Primary Health Center of Kembiritan Banyuwangi Regency - Rizki Yulia Purwitaningtyas; I Wayan Gede Artawan Eka Putra; Dewa Nyoman Wirawan (Universitas Udayana, 2015)
Background and purpose: Number of patients with type 2 diabetes mellitus in Kembiritan Primary Health Center has increased as many as 160 in 2013 to 215 in 2014. This study was conducted to determine risk factors of poor glycaemic control among patients with type 2 diabetes mellitus in the Primary Health Center of Kembiritan Banyuwangi. Methods: The research design was a case control study of 55 patients with poor glycaemic control of diabetes mellitus as cases and 55 patients with good glycaemic control of diabetes mellitus as controls (1:1), who were randomly selected from the registers of patients with diabetes mellitus at the primary health center during 2014. Data was collected through interviews at the primary health center during March-May 2015 using questionnaires. Data was analyzed by univariate, bivariate (chi square test) and multivariate using logistic regression. Results: Bivariate analysis showed that duration of disease and nutritional status significantly increase risks of poor glycaemic control respectively with OR=2.9 (95%CI: 1.20-7.54) and OR=5.7 (95%CI: 1.82-21.04). Multivariate analysis showed four factors that increase the risk of poor glycaemic control, namely duration of disease with adjusted OR=3.8 (95% CI: 1.37 to 10.59), medication adherence, with adjusted OR=3.7 (95% CI : 1.30 to 10.59), nutritional status, with adjusted OR=6.6 (95%CI: 2.01-21.44) and distance of health facilities, with adjusted OR=3.1 (95%CI: 1.19-7.95). Conclusion: Risk factors for poor glycaemic control among patients with type 2 diabetes mellitus were disease duration, adherence of medication, nutritional status and distance to health facilities.